Catalytic properties of cellulases and hemicellulases produced by Lichtheimia ramosa: Potential for sugarcane bagasse saccharification - Garcia, Nayara Fernanda Lisboa; Santos, Flávia Regina da Silva; Bocchini, Daniela Alonso [UNESP]; Paz, Marcelo Fossa da; Fonseca, Gustavo Graciano; Leite, Rodrigo Simões Ribeiro (Elsevier, 2018)
The use of microbial enzyme cocktails for the conversion of polysaccharides of plant origin into fermentable sugars is a global trend. The objectives of this study were to optimize the production of cellulases and hemicellulases by the fungus Lichtheimia ramosa, evaluate the catalytic properties of the produced enzymes, and apply these biocatalysts in the saccharification of sugarcane bagasse. The production of carboxymethylcellulase (CMCase), β-glucosidase, xylanase, and β-xylosidase by L. ramosa were 168.1 ± 2.2, 270.4 ± 8.9, 34 ± 0.8, and 199.2 ± 2.6 U/g of dry substrate, respectively. The optimum pH for the activity of the enzymes ranged between 4.5 and 5.5, and the optimum temperature varied between 55 °C and 65 °C. The enzymes were stable within a wide range of pH, and approximately 95% of their original activity was preserved when incubated for 1 h at 55 °C. The half-lives (t1/2) of CMCase, β-glucosidase, xylanase, and β-xylosidase were 68, 59, 52, and 54 min, respectively, when incubated at 60 °C. The enzymes were stable in solutions containing ethanol (10%), and the kinetic parameters (Km and Vmax) demonstrated that β-glucosidase from L. ramosa was competitively inhibited by glucose. The enzyme extract produced by L. ramosa was used for the saccharification of sugarcane bagasse pretreated with glycerol and the highest yield of glucose (10.66%) was obtained at 24 h of hydrolysis. The characteristics of the enzymes, combined with the efficiency in hydrolyzing sugarcane bagasse, allow for the application of this enzyme extract to processes of cellulose saccharification for the production of second-generation ethanol.
Keywords: Cellulolytic and hemicellulolytic complex; Enzymatic saccharification; Saccharification of vegetable biomass; Solid-state fermentation